HERNIOTOMY WHILE VENTRAL HERNIA AND ABDOMINOPLASTY - V. V. Plechev; O. V. Popova; V. 0. Sorokina; 0. S. Popov (Креативная хирургия и онкология, 2017)
The paper  presents materials  of investigations directed to improvement of results  of ventral  herniotomy. Traditional  hernial  gate  plasty  supplemented with  abdominoplasty is needed and  grounded. This combination allows to  decrease significantly  the  number of nearest and remote complications and to reach better esthetic operative results. The opportunity of using apparatus HAEMO-MENTICS PCS-2 for perfection of treatment was studied. The suggested technique permits to reduce the number of nearest postoperative complications by 2,5 times and to receive good cosmetic  result in 84% of patients.